CZTSe solar cells developed on polymer substrates: Effects of low‐temperature processing. (5th October 2017) - Becerril‐Romero, Ignacio; Acebo, Laura; Oliva, Florian; Izquierdo‐Roca, Víctor; López‐Marino, Simón; Espíndola‐Rodríguez, Moisés; Neuschitzer, Markus; Sánchez, Yudania; Placidi, Marcel; Pérez‐Rodríguez, Alejandro; Saucedo, Edgardo; Pistor, Paul
Abstract: Cu2 ZnSn(S1−x Sex )4 solar cells are well suited for roll‐to‐roll mass production since they are formed mainly by non‐toxic and earth‐abundant elements. Polyimide (PI) has proved to be a promising roll‐to‐roll compatible substrate yielding very high efficiency devices for Cu(In, Ga)Se2 . In this work, we demonstrate the feasibility of using PI as a low‐weight and flexible alternative to soda‐lime glass for Cu2 ZnSnSe4 (CZTSe) solar cells. Two main concerns arise when working with PI. Firstly, its low thermal robustness limits process temperatures below 500°C. The second concern is the lack of alkali in PI in contrast to conventional soda‐lime glass fundamental for high efficiency devices. This work tackles both issues. First, different alkali doping strategies are investigated for the incorporation of Na and K into CZTSe absorbers prepared on PI substrates by sequential precursor sputtering and selenization at 470°C: pre‐absorber synthesis and post‐deposition treatment. Post‐deposition treatment does not lead to an improvement of performance. Pre‐absorber synthesis effectively dopes the CZTSe absorbers increasing the solar cell performance and carrier concentration of the devices. Cu2 ZnSnSe4 devices are then fabricated on glass and PI at different temperatures (450°C‐490°C). A detrimental SnSe2 secondary phase is detected in most of these devices. The formation of this phase is proved to be strongly related to process temperature. Despite this, a 6.4% efficiency device is achieved at 490°C on glass. Finally, through further experimentation and the addition of a Ge nanolayer, we report a 4.9% efficiency flexible device on PI setting a new record for kesterite solar cells on a polymer substrate. Abstract : This work explores the fabrication of Cu2 ZnSnSe4 solar cells on polyimide and on soda‐lime glass at temperatures below 500°C. A 4.9% efficiency solar cell is achieved setting a record for a kesterite device fabricated on a polymer substrate. However, working at low temperature promotes the formation of SnSe2 both on glass and on polyimide. This secondary phase is found to be strongly related to process temperature and to be detrimental for the devices by creating shunting paths.